Synthesis and Crystal Structure of a New Cd(II) Coordination Polymer Based on Phthalic Acid and bis(imidazole) - Gao, Ronghua (Asian Journal of Chemistry, 2012)
One new coordination polymer [Cd2(PAA)2(bib)]n (H2PAA= phthalic acid and bib= 4,4'-bis (2- methylimidazol-1-ylmethyl)biphenyl) has been synthesized by the hydrothermal method and characterized by X-ray single crystal diffraction. In compound [Cd2(PAA)2(bib)]n, the phthalic acid ligand acts as bridging ligands exhibiting two coordination modes to link metal ions: bis-monodentate and bidentate chelating/bridging modes. The carboxylic groups bridge Cd(II) ions to an infinite 1D framework. The 4,4'-bis (2-methylimidazol-1-ylmethyl)biphenyl) ligands coordinate to two Cd(II) centers to give rise to a two-dimensional net.